Feasibility study of percutaneous thoracic duct embolization with lower-limb intermittent pneumatic compression devices - Ravivarma Balasubramaniam; Mona Mossad (Diagnostic and Interventional Radiology, 2023)

(untitled)
PURPOSETo demonstrate intranodal thoracic duct embolization (TDE) for treating chyle leaks following thoracic surgery and the feasibility of applying lower-limb intermittent pneumatic compression devices during TDE.METHODSBetween December 2017 and October 2020, 12 consecutive TDEs for post-operative chyle leaks were performed in 11 patients using intranodal lymphangiogram (IL) with an intermittent pneumatic compressive device applied to the lower limb. The procedure’s duration, technical/clinical success, and complications were retrospectively evaluated.RESULTSIL was successful at imaging the thoracic duct in all procedures (100%), and TDE had an intention- to-treat success rate of 92% (11/12). No related complications were observed during follow-up, which took place at a mean of 27 days. The time from the commencement of lymphangiogram until visualization of the thoracic duct was a mean of 21.6 min, and the mean overall procedure time was 87.3 min.CONCLUSIONThis study supports IL-guided TDE as a safe and effective option to treat post-thoracic surgery chyle leaks. We revealed shorter lymphangiogram times compared with previously published studies, and we postulate that the application of intermittent lower-limb pneumatic compressive devices contributed toward this study’s results by expediting the return of lymph from the lower limb. This study is the first to illustrate this approach in TDE and advocates for randomized controlled studies to further evaluate the influence of intermittent pneumatic compressive devices on the procedure.